STRATEGI PENINGKATAN KUALITAS BACA TULIS AL-QUR’AN DI TAMAN PENDIDIKAN AL-QUR’AN NURUL MUSTHOFA MANGLIAWAN WENDIT MALANG - Firda Nisa; Nur Hasan; Indhra Musthofa (VICRATINA, 2020)
Strategy is the most important reference held by teachers to achieve what is expected in a formal or non-formal education process. In this case the strategy of the Al-Qur’an Education Park or TPQ must adjust to the environment and existing conditions, so that during the teaching and learning process does not occur saturation of both the teacher and students. A goal can be achieved if the strategy in the process is also going well, there for in an educational institution must have the right strategy both in terms of learning and management. For this reason TPQ Nurul Musthofa must also have a good learning strategy to improve the quality of reading and writing Al-Qur’an or BTQ. To achieve these objectives in his research researchers used a type of qualitative research, with data collection procedures carried out include observation, interviews by conducting question and answer verbally with research sources, and documentation in the form of matters concerning research raised such as photographs, notes, reports, and so on.